KETERLIBATAN INDUSTRI DALAM PENGEMBANGAN KURIKULUM SEKOLAH MENENGAH KEJURUAN (SMK) UNTUK MENINGKATKAN KOMPETENSI LULUSAN - Wildan Habibi, Mohammad; Berlian Ananda Apriliana; Muhammad Faiz Risqullah Ramadhan; Mochammad Ardian Putra Prayoga; Faiza Yasmine Butsaina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Vocational High Schools (SMK) play a strategic role in preparing competent graduates who are ready to enter the workforce. However, there remains a gap between graduates’ competencies and the needs of the business and industrial sectors (DUDI), which continue to evolve dynamically. Therefore, industry involvement in the development of SMK curricula is a key strategy for enhancing the relevance of vocational education to the demands of the workforce. This study aims to examine the role and forms of industry involvement in the SMK curriculum development process to improve graduate competencies. The research method used is a literature review analyzing various scientific articles and research findings related to partnerships between schools and industry in the field of vocational education. The results of the study show that industry involvement can be carried out through various forms of cooperation, such as aligning curricula based on industry needs, implementing industrial work practices (Prakerin), developing industrial classes, and industry participation in evaluating student competencies. This collaboration is able to increase the relevance of learning material to the needs of the world of work, strengthen technical and non-technical skills such as work discipline, communication and adaptability, and increase graduates' work readiness.